Allogeneic Hemopoietic Stem Cell Transplantation for Myelofibrosis: 2021 - Bacigalupo, Andrea; Innocenti, Idanna; Rossi, Elena; Sora, Federica; Galli, Eugenio; Autore, Francesco; Metafuni, Elisabetta; Chiusolo, Patrizia; Giammarco, Sabrina; Laurenti, Luca; Benintende, Giulia; Sica, Simona; et al. (Frontiers in Immunology, 2021)
The aim of this review is to update the current status of allogeneic hemopoietic stem cell transplants (HSCT) for patients with myelofibrosis (MF). We have first summarized the issue of an indication for allogeneic HSCT, discussing several prognostic scoring systems, developed to predict the outcome of MF, and therefore to identify patients who will benefit of an allogeneic HSCT. Patients with low risk MF are usually not selected for a transplant, whereas patients with intermediate or high risk MF are eligible. A separate issue, is how to predict the outcome of HSCT: we will outline a clinical molecular myelofibrosis transplant scoring system (MTSS), which predicts overall survival, ranging from 90% for low risk patients, to 20% for very high risk patients. We will also discuss transfusion burden and spleen size, as predictors of transplant outcome. The choice of a transplant platform including the conditioning regimen, the stem cell source and GvHD prophylaxis, are crucial for a successful program in MF, and will be outlined. Complications such as poor graft function, graft failure, GvHD and relapse of the disease, will also be reviewed. Finally we discuss monitoring the disease after HSCT with donor chimerism, driver mutations and hematologic data. We have made an effort to make this review as comprehensive and up to date as possible, and we hope it will provide some useful data for the clinicians.